Students' perceptions on employability skills :a study of UNIMAS final year students - Salbiah, Salleh (2006)
The purpose of this study is to analyse studentsʼ understanding of the concept of employability skills and their perceptions on the importance of employability skills to secure employment, to effectively perform in the workplace as well as retain employment, and to assess their level of competency with respect to these employability skills. Questionnaires were used to collect data from 322 final year undergraduates of Universiti Malaysia Sarawak (UNIMAS).